TOXICOLOGICAL SCREENING OF A NOVEL SIDDHA POLYHERBAL FORMULATION “SIRINGIPAERATHI CHOORANAM” - R., VIJAYANIRMALA; R., ABINAYA; V., VELPANDIAN (International Journal of Current Pharmaceutical Research, 2019)
Objective: The aim of the present study is to validate the safety efficacy of “Siringipaerathi Chooranam” (SPC) in acute and sub-acute studies in the animal model. Methods: Siddha system of medicine is the one of the earliest systems of medicine, which was practiced by our spiritual scientists. It constitutes plants, animals, metals and mineral formulations. Chooranam are fine to dry powders of drugs. Hence I have preferred to choose “Siringipaerathi Chooranam” (SPC) which is indicated for hepatoprotective activity and it was prepared as per the classical Siddha literature. The adult wistar albino rats were used for acute toxicity for 14 d and sub-acute studies for 28 d as per OECD guidelines 423 and 407. The test drug was made Suspension with 2% CMC with uniform mixing and was administered to the groups of Wistar albino rats. The drugs were orally administered to the dosage in the levels of 100, 200 and 2000 mg/dose in acute and subacute studies. The ingredients of SPC are Inji (Zingiber officinalis), Milagu (Piper nigrum), Thippili (Piper longum), Thipili moolam (Root of Piper longum), Lavanga pathiri (Cinnamomum tamala),Elam (Elettaria cardamomum), Kodiveli ver (Plumbago zeylanica), Lavanga pattai (Cinnamomum zeylanicum), Moongil uppu (Bambusa arundinaceae), Sandhana thool (Santalum album), Vilamichu-ver (Plectranthus vettiveroides), Sathikkai (Myristica fragrans), Seeragam (Cuminum cyminum), Kirambu (Syzygium aromaticum), Sugar (Saccharum officinarum), Nei (Ghee). Results: The present investigation shows that there were no significant toxicity changes seen during the study. The body weight, food, water intake, behavioral, CNS, ANS, CVS, Vitals, Hematology, Biochemical and Histopathology of kidney, liver, spleen were observed both in control and test group animals were appears to be normal range. Conclusion: Thus the authors conclude from the results that the safety efficacy of SPC through acute and sub-acute toxicity studies in rodents.